Standardization of Terms for Silvicultural Systems in India - Krishna Swamy, S. (Indian Forester, 1958)
A perusal of publications and working plans from different States of the Union, brings to light a considerable variety of terms not officially recognized by Silvicultural Conferences, to designate and describe Silvicultural Systems prescribed. By way of illustration, a few selected samples are given. These are discussed in brief, and critically analysed with a view to ascertaining whether they fulfil the requirements of a Silvicultural System. It appears that the mushroom growth of Silvicultural Systems is attributable, to a great measure, to our present inadequate criteria for the recognition of a Silvicultural System. A suggestion is, therefore, made for a more comprehensive concept of a System in order to effectively standardize the approach, for use in the Indian Union.